Delay discounting in opioid use disorder: Differences between heroin and prescription opioid users. (1st December 2016) - Karakula, Sterling L.; Weiss, Roger D.; Griffin, Margaret L.; Borges, Allison M.; Bailey, Allen J.; McHugh, R.Kathryn
Highlights: Delay discounting is the tendency to overvalue immediate vs. delayed reward. Adults with opioid use disorder completed a measure of delay discounting. Prescription opioid (PO) users had lower delay discounting vs. heroin users. Any use of heroin was associated with greater delay discounting than POs alone. Heroin use is associated with a more impulsive style of decision-making. Abstract: Background: Among those with opioid use disorder, heroin use is associated with poorer prognosis relative to use of prescription opioids alone. However, relatively little is known about distinguishing features between those who use heroin relative to those who use prescription opioids. In the present study we evaluated differences in delay discounting in those with opioid use disorder based on primary opioid of use. Delay discounting is associated with a range of negative outcomes and is an important therapeutic target in this population. Methods: Treatment-seeking adults with opioid dependence completed self-report measures including past-month opioid use and the Monetary Choice Questionnaire (Kirby and Marakovic, 1996; Kirby et al., 1999), a measure of delay discounting. Participants were divided into two groups based on whether they used any heroin in the past 30 days or only prescription opioids, and delay discounting scores were compared between the groups. Group differences in sociodemographic or clinical variables were included in the analysis as covariates. Results: Results from a forward stepwise linear regression indicated that heroin use was associated with significantly higher delay discounting ( B  = −0.99, SEB  = 0.34, t  = −2.88, p  = 0.005), even when considering covariates. Conclusions: Adults with opioid dependence who exclusively used prescription opioids had lower delay discounting relative to those who used heroin. This finding contributes further to the literature suggesting that heroin use is associated with greater clinical severity among those with opioid use disorder.